2007
DOI: 10.1007/s10340-007-0187-4
|View full text |Cite
|
Sign up to set email alerts
|

Antifeedant activity and toxicity of leaf extracts from Porteresia coarctata Takeoka and their effects on the physiology of Spodoptera litura (F.)

Abstract: Antifeeding and toxic eVects of chemical extracts from Porteresia coarctata Takeoka on the insect pest Spodoptera litura (F.) were investigated in the laboratory. Hexane extracts of P. coarctata leaves were re-dissolved in dimethyl sulfoxide and applied in water to leaves of Ricinus communis L. (castor). A concentration of 1,000 and 2,000 ppm extract exhibited signiWcant antifeeding and toxic eVects to third instar larvae when compared to the same concentration of dimethyl sulfoxide in water as control. One da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 22 publications
1
20
0
2
Order By: Relevance
“…Increased surface wax levels were correlated with resistance of cabbage (Brassica oleracea L.) to the aphid, Bravicoryne brassicae L., of sorghum (Sorghum bicolour L.) to the green bug Schizaphis graminum (Rondani), of winter wheat (Triticum aestivum L.) to the English grain aphid S. avenae (F.) [1]. Similarly, Ulrich et al [31] showed the insecticidal and antifeedant properties of Porteresia coarctata Takeoka leaf extract against the generalist pest Spodoptera litura (F.), leading to biochemical changes in the insect body. The chemicals have also been attributed with benefi cial properties as they necessarily represent the fi rst line of contact with organisms [3,11].…”
Section: Discussionmentioning
confidence: 84%
“…Increased surface wax levels were correlated with resistance of cabbage (Brassica oleracea L.) to the aphid, Bravicoryne brassicae L., of sorghum (Sorghum bicolour L.) to the green bug Schizaphis graminum (Rondani), of winter wheat (Triticum aestivum L.) to the English grain aphid S. avenae (F.) [1]. Similarly, Ulrich et al [31] showed the insecticidal and antifeedant properties of Porteresia coarctata Takeoka leaf extract against the generalist pest Spodoptera litura (F.), leading to biochemical changes in the insect body. The chemicals have also been attributed with benefi cial properties as they necessarily represent the fi rst line of contact with organisms [3,11].…”
Section: Discussionmentioning
confidence: 84%
“…Several authors have reported that plant extracts possess similar type of antifeedant activity against Helicoverpa armigera (Raja et al, 2005;Baskar et al, 2009;Akhtar and Isman, 2004). Some compounds present affect the feeding behaviour of the insects and inhibit feeding,while others disrupt hormonal balance (Ulrichs et al, 2008). Some plants have been reported as insect repellents, antifeedants, insecticides, ovicides and oviposition deterrents (Dubey et al, 2010 ).…”
Section: Resultsmentioning
confidence: 99%
“…The active ingredients in neem have the ability to function at hormonal concentrations and produce ecdysone-type effects in susceptible insects (Govindachari et al, 2004). Ulrichs et al (2008) reported that the third instar larvae of Spodoptera litura fed on castor leaves treated with salt grass Porteresia coarctata (Roxb.) leaf extract at different concentrations showed significant reduction in protein and DNA content in the fat body and midgut tissues.…”
Section: Ash Gourd Benincasa Hispida L Is One Of the Important Cucurmentioning
confidence: 99%